Hagiography and Invention in Plácido (1871), a novel by Francisco Campos - Carrasco, Patricia G. (2011)
In Plácido (1871), Francisco Campos utilized hagiography and rhetoric as a means to articulate thought. This was his way to promote social action in order to confront the difficulties of his reality. He used this form of writing in order to disseminate his message and thus contribute as a committed intellectual to the creation of ideal subjects for the national state.